Risk factors for infections in patients with lupus nephritis and construction of a prediction model - Liu Ding-lin; Zhang Wen-hao; Hu Hao-fei; Li Ai-ting; Chen Zhi-jin; Zheng Cai-yan; Qin Le-le; Zhang Li; Li Rui-zhao; Ye Zhi-ming (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the risk factors for infection in lupus nephritis （LN） after starting immunosuppressive therapy.MethodsA total of 374 patients who were diagnosed with LN and received immunosuppressive therapy at Guangdong Provincial People's Hospital （Guangdong Academy of Medical Sciences），Southern Medical University from January 1， 2000 to December 31， 2020 were retrospectively collected. The basic conditions of the patients， renal pathologic indexes， baseline and changes in biochemical and immunologic indexes， and the occurrence of infections during follow-up were collected. Cox proportional risk regression model was used to analyze the factors affecting secondary infections.ResultsThe mean age of the included patients was （30 ± 12）years， and 85.3% of them were female. The mean follow-up period was 2 years. During the follow-up， 219 （58.6%） LN patients developed infections. Multifactorial Cox proportional risk regression model analysis showed that baseline IgM （HR=1.288，95% CI： 1.074-1.544， P=0.006） and free light chain λ levels （HR=1.783，95% CI： 1.000-3.177， P=0.050） were the risk factors for secondary infections in LN patients， whereas the reduction of double-stranded DNA （dsDNA） at 3 months of treatment （HR=0.728， 95% CI： 0.563-0.924， P=0.016） and hemoglobin elevation （HR=0.790，95% CI： 0.652-0.958， P=0.017） were protective factors for infection. After standardizing the variables and excluding patients with infections within 3 months， a multivariate analysis was performed， and a nomogram was constructed. The receiver operating characteristic （ROC） curve was plotted， and the area under the curve （AUC） of the nomogram was 0.825.ConclusionPatients with LN have a higher incidence of infections during the treatment period. High baseline levels of IgM and serum light chain λ are associated with an increased risk of infection after immunosuppressive therapy in LN patients， whereas a decrease in dsDNA antibodies and an increase in hemoglobin are associated with a decreased risk of infection in patients with LN within 3 months of treatment. The nomogram constructed in this study has a good predictive ability for the occurrence of risk factors for infection in LN patients.